Geochemistry of Geologic CO2 Sequestration - Bourg, Ian C.; Cole, David R.; DePaolo, Donald J.; Navrotsky, Alexandra (Reviews in mineralogy and geochemistry, 2018)
Volume 77 of Reviews in Mineralogy and Geochemistry focuses on important aspects of the geochemistry of geological CO2 sequestration. It is in large part an outgrowth of research conducted by members of the U.S. Department of Energy funded Energy Frontier Research Center (EFRC) known as the Center for Nanoscale Control of Geologic CO2 (NCGC). Eight out of the 15 chapters have been led by team members from the NCGC representing six of the eight partner institutions making up this center - Lawrence Berkeley National Laboratory (lead institution, D. DePaolo - PI), Oak Ridge National Laboratory, The Ohio State University, the University of California Davis, Pacific Northwest National Laboratory, and Washington University, St. Louis.